Cloning and characterization of B-1, 3-glucanase gene from different clones of Hevea brasiliensis - Supriya R; Saleena A; Thulaseedharan A (Placrosym XVII, 2006, Kochi, India. Journal of Plantation Crops, 34 (3). Indian Cardamom Research Institute (Spices Board), Idukki, India, pp.572-575.)
The relative tolerance of plants towards a particular disease/pathogen is mainly determined by the interactions between the disease resistant R genes and the associated pathogen avirulence avr genes, affecting the plant. B-1, 3-glucanase enzyme, which belongs to the category of PR-2 (pathogenesis related proteins) family is known to be involved in the plant defence reactions against pathogens like Phytophthora causing abnormal leaf fall disease (ALF) in rubber plantations. The present work was undertaken to characterize the genomic DNA sequences coding for B-1, 3-glucanase from different clones of Hevea brasiliensis. High quality genomic DNA was isolated from Hevea clones, FX 516, RRII 105, RRII 33, PR 107, PB 86 and RRIM 701. B-1, 3-glucanase genomic sequences were PCR amplified using oligonucleotide primers designed based on previously reported sequences. A PCR product with approximately 1.3 Kb in size was amplified from all the clones. The isolated gene was later cloned in the Topo TA* cloning vector, sequenced and analysed for sequence variations. The result shows major variations within the intronic sequences. CT repeats within the intronic sequences show deletion/insertions among the clones studied. Although, the differences occur in the number of deletions, the location is almost similar. Only minor variations in nucleotides were observed in the exons. Though, the exact role of introns in a particular gene is not completely known, it is reported that through alternative splicing and non-sense mediated mRNA decay; the introns play an important role in the expression of a particular gene.
Keywords: Abnormal leaf fall disease; B-1, 3-glucanase; Genomic sequences; Intron deletions